The Rise of Civilization and the Beginning of History in Europe – Deconstructing Outmoded Concepts of ‘Prehistory’ - Haarmann, Harald (Zeitschrift für Balkanologie, 2023)
Traditional scholarship on how civilization emerged in Europe is outmoded and new insights call for revision. Ancient Greek civilization was not the earliest advanced culture in southeastern Europe, nor was it the Minoan civilization of ancient Crete. Following the cliché of ex oriente lux (“light from the East”) all major achievements of humankind spread from Mesopotamia in the Middle East. Modern archaeology, cultural science and historical linguistics indicate that civilizations did not originate from a single prototype. Several models produced divergent patterns of advanced culture. It may come as a surprise to many readers that the earliest model of an advanced culture in fact emerged in southeastern Europe, in the course of the sixth millennium BCE. This civilization is known by the name Old Europe, or Danube civilization, respectively. The major achievements of this early civilization will be highlighted in this contribution.